Exploring the Influence of Elements of the Social and Physical Environment on Neighborhood Gun Crime - Thomas, Shaun A. (American journal of criminal justice, 2022)
Amidst the more than 38,000 firearm related deaths in the United States annually, academic researchers, policy makers, and the general public often lack a basic understanding as to how elements of the physical environment work alongside socio-demographic characteristics of neighborhoods to influence the occurrence, prevalence, and spatial patterns in gun crime. Drawing on criminal justice, public health, and business databases in 2015-2018, we examine whether, and how, aggregate risk from the physical/built environment works independently and in conjunction with socio-structural features of neighborhoods to predict gun-related criminal incidents. Our results suggest: (1) a neighborhood-level measure of risk based on elements of the physical or built environment is associated with exacerbated levels of neighborhood gun crime; (2) racial heterogeneity/diversity and the concentration of disadvantage increase the risk of gun crime, as well; (3) both racial diversity and concentrated disadvantage condition the impact of the neighborhood built environment such that risk associated with the physical landscape is more strongly associated with gun crimes in racially homogenous and more affluent locales; and (4) the influence of the physical environment on risk of gun-involved criminal incidents is non-linear with a positive yet decelerating slope. Implications for gun violence stakeholders and the further development of research on neighborhood-level measures of risk from the physical built environment are discussed.